Sequência didática investigativa de bioética em genética: temas e dilemas no ensino de Biologia - PACÍFICO, Camila Marreira (Universidade Federal do Pará, 2022)
The present work consists of the elaboration of an Investigative Didactic Sequence (SDI) for the teaching of Bioethics in Genetics, in the context of Biology contents for high school. The objective is to promote the teaching of bioethics through varied resources and strategies, based on investigative teaching. The methodological approach chosen to work on this theme was the investigative approach, which gave rise to the product entitled: TEACHING BIOETHICS IN GENETICS: Investigative Didactic Sequence for High School. In final, non-conclusive terms, it can be seen that some steps are fundamental for the elaboration of a product with a focus on a teaching and learning process for the context of studies in Biology, such as: Knowing the characteristics of an SDI, for bibliographic survey; define the aspects of investigative education that would be covered in the SDI and the choice of topics to be addressed in the SDI. In addition, the structuring of an SD implies that each moment and the steps of an SDI must be properly presented in the format of guidance for the teacher, explaining intended objectives, the duration of the activities, the place where they are carried out, the material resources, didactic and methodological methods, the applied methodology and the evaluation proposal. Investigative teaching should be the structuring axis of SD, which is why it is necessary to define common characteristics in the literature, such as: choice of the object of study and problematization, expression of students' previous ideas and projection of hypotheses, construction and communication of new information produced by students and, finally, scientific expression and communication.